ENSO and IOD Variability: Impacts on Precipitation and Sea Surface Temperature in Bali and NTB - Deshafa, Abdul Fadhilla (The Physical Society of Indonesia, 2025)
This study investigated how interactions between the El Niño–Southern Oscillation and the Indian Ocean Dipole influenced sea surface temperature and rainfall variability in Bali and West Nusa Tenggara. Monthly sea surface temperature, precipitation, and wind data from January 2004 to August 2022 were analyzed using reanalysis and satellite-derived datasets alongside indices of oceanic and dipole variability. Five representative climate phase combinations were identified to capture neutral, wet, and dry conditions. Statistical and spatial analyses demonstrated that coupled El Niño and positive dipole phases produced the strongest cooling of sea surface temperatures (up to 1.2 °C below average) and the most severe rainfall deficits (exceeding 10 mm per day). Conversely, La Niña with positive dipole phases yielded enhanced wet-season rainfall (up to 13 mm per day). These findings showed that phase interactions modulated monsoonal moisture supply, informing water resource management and climate adaptation in coastal Indonesia